A novel approach for optimal economic dispatch scheduling of integrated combined heat and power systems for maximum economic profit and minimum environmental emissions based on Benders decomposition. (1st May 2016) - Sadeghian, H.R.; Ardehali, M.M.
Abstract: The utilization of energy efficient CHP (combined heat and power) systems provides opportunities for GENCOs (generation companies) to simultaneously increase their economic benefits and decrease environmental emissions. The goals of this study are to develop and simulate a novel approach for optimal economic dispatch scheduling for a GENCO to maximize economic profit and minimize environmental emissions based on integration of CHP systems with conventional TG (thermal power generating) units, where a DBD (double Benders decomposition) solution approach is proposed for optimization. The CHP PBUC (profit based unit commitment) problem with non-convex constraints for integration of CHP units into GENCOs generation portfolio is solved and, the results for several cases along with sensitivity analyses are reported. The results from DBD approach for optimization are validated based on comparison with those from gravitational search and imperialistic competitive algorithms as well as other algorithms examined in other studies. When CHP units are integrated with a 10-TG unit system, results from implementing the proposed DBD approach are extremely encouraging, as GENCO profit for providing electricity and heat energy is increased by 518.78% and environmental emissions are reduced by 7.57%, in comparison with case of GENCO using TG units for meeting the same electricity demand. Highlights: Utilization of CHP units allows for participation in heat and electricity markets. Optimal scheduling of CHP is formulated based on economic profit and emissions. Multi-objective profit based unit commitment for CHP integration is optimized. Double Benders decomposition approach introduced for optimization is efficient. CHP integration leads to higher profit by 518% and lower emissions by 7.57%.